Classroom Management Strategies in Creating a Joyful Learning Environment in Madrasah Tsanawiyah - Fitri Fitri; Muhammad Hasbi; Ratna Ratna; Nadia Sudirman; Muh. Syakur; Dirmansyah Dirmansyah; Husnul Khatimah Annisa; Zahriyani Zahriyani; Muh. Fahri Khaeruddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Rigid and monotonous classroom management at the Madrasah Tsanawiyah level often becomes an obstacle to achieving effective learning, which results in low student motivation and engagement in the classroom. This phenomenon requires a transformation of teacher strategies to create a more dynamic and supportive learning atmosphere. This study aims to analyze classroom management strategies implemented by teachers in creating a joyful learning environment and evaluate their impact on the academic climate at Madrasah Tsanawiyah. This study uses a mixed methods approach with a triangulation design. The research subjects involved students in grades 9.1 (n=15) and 9.2 (n=13) at MTs As'adiyah Cabenge. Quantitative data were collected through a questionnaire on student perceptions regarding learning comfort, while qualitative data were obtained through classroom observations and in-depth interviews with teachers regarding spatial arrangement techniques, interaction management, and positive reinforcement. The research findings indicate that the implementation of the Joyful Learning strategy through flexible seating arrangements, icebreaker integration, and a personalized approach can significantly increase student engagement scores in both classes. The results of the data analysis show that despite the relatively small number of students (a total of 28 students), a joy-centered classroom management approach is effective in reducing learning anxiety and increasing cohesion among students at MTs As'adiyah Cabenge. Theoretically, this study strengthens the literature on the urgency of affective-based classroom management in religious schools. Practically, this study provides strategic guidance for educators at Madrasah Tsanawiyah to design a hidden curriculum that prioritizes students' psychological well-being without neglecting academic discipline.